A Review of Depression of College Student: Symptoms, Types, Contributing Factors: Exploring the Impact of Depression on College Students: A Focus on Symptoms, Types, and Contributing Factors in India's Engineering Education (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Psychological distress is mainly referred to as a measure of people's mental health and is widely used as an indicator in population surveys, public health evaluations, epidemiological research, or related clinical investigations and other important intervention research. The scientific literature highlights the applicability to the indistinguishable group of symptoms of depression, general anxiety, behavioural problems, functional limitations and even personality characteristics of psychological discomfort. India engineering education has seen remarkable development over the last decade in the number of students and the number of institutions, but the average quality of schools and graduate students is suspicious, as shown by the human resources survey of Indian multinational companies, the employability of only one quarter of engineering graduates is eligible. Lack of communication skills, lack of quality education, lack of practical knowledge, lack of interpersonal skills, a bad position in leadership, teamwork and time management are the main reasons of the bad category of pupils. In this paper discuss the about Depression, Symptoms, types of depression, and treatment of depression.